2020
DOI: 10.1029/2020wr027719
|View full text |Cite
|
Sign up to set email alerts
|

Local and Reach‐Scale Hyporheic Flow Response From Boulder‐Induced Geomorphic Changes

Abstract: Stream hydromorphology regulates in-stream water flow and interstitial flow of water within streambed sediments, the latter known as hyporheic exchange. Whereas hyporheic flow has been studied in sand-bedded streams with ripples and dunes and in gravel-bedded streams with pool-riffle morphology, little is known about its characteristics in plane bed morphology with subdued streambed undulations and sparse macroroughness elements such as boulders and cobbles. Here, we present a proofof-concept investigation on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 71 publications
0
25
1
Order By: Relevance
“…The authors reported that the induced morphological changes had greater effect on hyporheic flows than boulders alone, concreting the influence of secondary bedform presented by Gordon et al (2013). Model limitations and simplification were reported in both Zhou & Endreny (2013) and Dudunake et al (2020) studies.…”
Section: Surface Feature Modificationmentioning
confidence: 94%
See 4 more Smart Citations
“…The authors reported that the induced morphological changes had greater effect on hyporheic flows than boulders alone, concreting the influence of secondary bedform presented by Gordon et al (2013). Model limitations and simplification were reported in both Zhou & Endreny (2013) and Dudunake et al (2020) studies.…”
Section: Surface Feature Modificationmentioning
confidence: 94%
“…Flume studies could control environmental factors, but efforts required was higher. Numerical models could achieve in depth assessment of hyporheic processes, isolate environmental factors and predict future outcomes, but was limited by assumptions, accuracy of measured data and system feedback to applied changes (Dudunake et al 2020). Jaeger et al (2019) suggested adoption of multi-feature multidisciplinary approach of study to reduce inadequacies and maximize research outputs.…”
Section: Methodology Selectionmentioning
confidence: 99%
See 3 more Smart Citations